Riboswitches as Potential Targets for the Development of Anti-Biofilm Drugs - A. Reyes-Darias, Jose; Krell, Tino (Current Topics in Medicinal Chemistry, 2017)
In nature, bacteria can exist as single motile cells or as sessile cellular community, known as microbial biofilms. Bacteria within biofilms are embedded in a self-produced extracellular matrix that makes them more resistant to antibiotic treatment and responses of the host immune system. Microbial biofilms are very important in medicine since they are associated with several human diseases such as dental caries, periodontitis, otitis media, infective endocarditis, infectious kidney stones, osteomyelitis or prostatitis. In addition, biofilms formed on the surface of clinical devices such as pacemakers, implants and catheters are difficult to treat, which underlines the clinical relevance of biofilm formation. At the molecular level, the switch from the planktonic state to biofilm formation is regulated primarily by bis- (3'-5)-cyclic dimeric guanosine monophosphate (c-di-GMP). C-di-GMP performs its function by binding to a wide variety of proteins, but also to riboswitches. C-di-GMP riboswitches are RNA regulatory elements located in the 5′-untranslated regions (5′-UTRs) of RNA messengers (mRNA) from genes involved in virulence, motility and biofilm formation, which are regulated by changes in the intracellular concentration of c-di-GMP. This review discusses the role of c-di-GMP responsive riboswitches as potential targets for the design of anti-biofilm agents.
Keywords: Riboswitch